2014
DOI: 10.1002/adfm.201403418
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Vertical Charge Transport in a Semiconducting P3HT Thin Film on Single Layer Graphene

Abstract: The crystallization and electrical characterization of the semiconducting polymer poly(3‐hexylthiophene) (P3HT) on a single layer graphene sheet is reported. Grazing incidence X‐ray diffraction revealed that P3HT crystallizes with a mixture of face‐on and edge‐on lamellar orientations on graphene compared to mainly edge‐on on a silicon substrate. Moreover, whereas ultrathin (10 nm) P3HT films form well oriented face‐on and edge‐on lamellae, thicker (50 nm) films form a mosaic of lamellae oriented at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
101
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 40 publications
5
101
0
Order By: Relevance
“…In 2014, an international research group reported, for the first time, that semiconducting polymer thin films' performance, in terms of vertical charge transport (i.e. parallel to thickness), is enhanced considerably when deposited on a single-layer graphene [14]. The importance of this work is that it contradicts the general notion that thinner polymer films conduct better.…”
mentioning
confidence: 93%
“…In 2014, an international research group reported, for the first time, that semiconducting polymer thin films' performance, in terms of vertical charge transport (i.e. parallel to thickness), is enhanced considerably when deposited on a single-layer graphene [14]. The importance of this work is that it contradicts the general notion that thinner polymer films conduct better.…”
mentioning
confidence: 93%
“…The crystallization kinetics of high‐density and low‐density polyethylenes on CNTs were also investigated by Depan et al . The induced crystallization of P3ATs onto graphenic materials was also widely reported; e.g. well‐oriented ultrathin P3HT films on graphene, a graphene oxide/P3AT mixture having semi‐spherulites, connecting the individual reduced graphene oxide (rGO) monolayers with P3HT nanowires 53 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Regioregular poly(3‐hexylthiophene) (P3HT) because of appropriate processability and electrical properties, good functionality and a high tendency to develop nanostructured crystals is also an attractive material for electronic devices such as organic field effect transistors and solar cells . It is demonstrated that for conjugated polymers like P3HT, the highest conductivity occurs along the polymer backbone and also through π – π stacking …”
Section: Introductionmentioning
confidence: 99%
“…The reduction of GO is the most efficient method for producing large amounts of reduced GO (rGO) . Suspensions of graphene and rGO have been utilized to nucleate P3HT nanofibers and modify the orientation of crystals in P3HT thin films . Hole transporter‐functionalized rGO and graphene–fullerene composite have also been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%